Controversies in Orthopaedic Trauma- Management of Fractures of Shaft of Femur in Children Between 6 and 12 Years of Age - Jain, A; Aggarwal, A; Gulati, D; Singh, MP (Kathmandu University Medical Journal, 2015)
The management of femoral shaft fractures in children is largely directed by the age and built of the child. There is wide consensus on the non operative treatment of children less than six years of age. Operative treatment is recommended for children more than 12 years of age, only the surgical options vary. The age group of 6-12 years remains a controversial area with multiple studies advocating different lines of treatment. We studied the literature on treatment of femoral shaft fractures in 6 to 12 year age group over the past 25 years through PubMed search and found 79 studies dealing with management of paediatric shaft femur fractures in this age group. Studies dealing with other age groups, animal studies and languages other than English were excluded. The treatment modalities included early or immediate hip spica, traction alone, external fixator, plating (open/minimally invasive), intramedullary nailing- rigid/flexible and intramedullary Kirschner wire. The short listed articles were studied for rate and time of union, complications such as non-union and malunion, leg length discrepancy, infection, implant impingement, refracture and cost analysis. Operative treatment is usually the preferred treatment option in this age group, as it decreases hospitalization time, decreases morbidity and allows early return of child to school. Flexible intramedullary nailing is recommended for length stable fractures. Submuscular bridge plating (minimally invasive) is reserved for comminuted fractures. External fixator is reserved for open fractures and initial stabilization of femoral shaft fractures in polytrauma pediatric patients. Intramedullary K wire is a viable option in resource contrained centres where specialized implants and instrumentation is not available. Kathmandu University Medical Journal Vol.12(1) 2014: 77-84